Non-thermal Technologies for Food Processing - Jadhav, Harsh Bhaskar; Annapure, Uday S.; Deshmukh, Rajendra R. (Frontiers in Nutrition, 2021)
Food is subjected to various thermal treatments during process to enhance shelf-life of food. But these thermal treatments may result in deterioration of nutritional and sensory qualities of food. With change in the lifestyle of people around globe their food needs have changed. Today’s consumer demand for clean and safe food without compromising nutritional and sensory qualities of food. This directed attention of food professionals towards development of non-thermal technologies which is green, safe and environment friendly. In non-thermal processing food is processed at a temperature near to room temperature, so that there is no damage to food because of heat and heat sensitive nutritious material is intact in the food contrarily to the thermal processing of food. These non-thermal technologies can be utilized for treating all kinds of food like fruits, vegetables, pulses, spices, meat, fish etc. Non-thermal technologies have emerged largely in the last few decades in food sector.